Hepatitis B Birth Dose among Children in District 2 Hospital, Ho Chi Minh City, Vietnam: Prevalence and Associated Factors - Giao Huynh; Thanh Binh Nguyen; Ngoc Nga Cao; Minh Hoang Phan; Thi Bich Hop Dang; Thi Ngoc Han Nguyen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. A birth dose of the hepatitis B vaccine will prevent most perinatally acquired infections and offers early protection from horizontal transmission. This article assessed the prevalence of the hepatitis B birth dose and associated factors among children in the District 2 Hospital. Methods. A prospective cross-sectional study between June and December 2017 recruited parents/caregivers of children aged 12–59 months who were randomly selected at the vaccination department in the District 2 Hospital. The structured questionnaire applied was to collect the characteristics of participants and check the vaccination schedule. The birth dose was defined as the hepatitis B vaccine, which was given to children within 24 hours after birth. Additionally, a semistructured questionnaire was used for interviews and focus group discussions (FGDs) to assess the risk perceptions and barriers to vaccination. Results. A total of 292 parents/caregivers had a mean age of 32.7 ± 6.8 years; among them, 88.7% were females. Their children had a mean age of 30.3 ± 13.9 months and 71.6% of these children received the hepatitis B birth dose, which correlated with the age of gestation (P<0.05). In-depth interviews and FGDs found that most participants did not know that hepatitis B could be transmitted through childbirth, and barriers that affected the birth dose vaccine included children being sick, premature infants, or reason relating to physicians. Conclusions. The rate of hepatitis B birth dose was low, which resulted from associated factors such as premature birth, likely to be linked with false contraindications and beliefs that, potentially, the 2013 incident is still fresh in people’s minds. Therefore, strategies to implement policies around the hepatitis B birth dose should be in line with current World Health Organization recommendations and strategies to modify current beliefs about vaccination.